Impacto do tabagismo no perfil inflamatório sistêmico de pacientes portadores de câncer de pulmão - Ferreira, Mariane Okamoto (2022)
Primary cancer (PC) is the cancer with the highest incidence and mortality worldwide in 1985 and smoking is the main modifiable carcinogenic factor for CP. It is known that cancer, as well as cigarette smoke and other tobacco derivatives, are generators of inflammation, producers of immune mediators, sources of free radicals and other components that deregulate the redox balance. However, their interrelationships are complex and the specific contribution of smoking to primary lung cancer remains to be clarified. Lung cancer is considerably affected by the immune response, which implies the participation of inflammatory signals such as the cytokines interleukin 12 (IL-12) and tumor necrosis factor alpha (TNF-α). These cytokines are the main regulators of response patterns immune and response of CD4+ T lymphocytes. Low levels of IL-12 and TNF-α have been related to anti-inflammatory responses (Th2), which implies responses associated with proliferation, metastasis and neoplastic chemoresistance. In this context, this study investigated the impact of smoking on the systemic circulating levels of oxidative stress mediators (lipoperoxides – LPO, nitric oxide metabolites – NOx and total antioxidant potential – TRAP), the cytokines TNF-α and IL-12, among smokers or non-smokers, in lung cancer and control individuals. The project was approved by the Ethics Committee in Research with Human Beings of Unioeste ̶ Francisco Beltrão. This is an exploratory and descriptive cohort study, carried out at Hospital do Câncer Francisco Beltrão, between November 2019 and August 2021. Statistical analysis was performed using the GraphPad Prism 7.0 software and a p-value <0.05 was considered significant. In the lung cancer group (n=20), mean age 54.2 years; men (68%), smokers or ex-smokers (77%), alcoholics or ex-alcoholics (50%). The control group (n=54), mean age 60.5 years, men (54%), smokers or former smokers (54%), had never drunk (54%). Cytokine measurements show a significant increase in circulating IL-12 only in healthy smokers (mean 57.81 pg/ml, min. 38.26 pg/ml, max. 70.71 pg/ml) compared to healthy non-smokers. smokers (mean 54.61 pg/ml, min. 48.16 pg/ml, max. 65.49 pg/ml - Mann-Whitney U test: Z=1.98; CI=97.64%) without change of TNF-α levels. Regarding the oxidative stress profile, smokers without cancer (mean NOx levels 28.75 µM; min. 33.5 µM; max. 23.93 µM and mean lipid peroxidation 671,877.4 µM; min. 267,360 µM; max. 963,159 .5 µM) had higher levels of oxidative stress compared to non-smoking controls (mean NOx levels 29.73 µM; min. 23.5 µM; max. 38.07 µM- Mann-Whitney U test: Z= 0 .04; CI= 51.49% and mean lipid peroxidation 335,659.5 µM; min 290,520 µM; max 957,903.5 µM - Mann-Whitney U test: Z=3.01; CI=99.87%). No differences were observed in the other groups. These results indicate that, in cancer-free individuals, smoking has a significant impact on inflammation, producing higher levels of LPO, NOx, and IL-12. In lung cancer patients, the inflammatory levels observed were similar regardless of the smoking factor, indicating that smoking itself did not have an additional impact on cytokines or oxidative stress profiles already produced by the disease.